PEMBELAJARAN NILAI-NILAI PENDIDIKAN KARAKTER PADA ANAK USIA DINI MELALUI FILM ANIMASI DI LAYAR TELEVISI DALAM PERSPEKTIF ISLAM - Moh Syamsi; Nur Khamim (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
Education has the function of developing cultural values and past achievements into national cultural values in accordance with present and future life and developing new achievements that become the new character of the nation. Education also plays an important role in ensuring the survival of the nation and state. Handling character in the family, of course, the role of parents is very large to realize the creation of good child character. Character education in the family and community environment can be done by introducing literary works such as films, fairy tale stories and novels. In this study, the type of research used was Library Research, using qualitative research methods with a phenomenological approach to describe the values of character education in a work of art in the form of an animated children's series on television.